Motivational Effects of Enhanced Expectancies for Motor Learning in Individuals With High and Low Self-Efficacy. Issue 1 (February 2020) - Ghorbani, Saeed; Bund, Andreas
Previous research has shown that enhanced expectancies can foster a person's motivational state and facilitate motor learning. However, the effects of enhanced expectancies on motivational state and subsequent motor learning in individuals with varied motivational states (e.g., self-efficacy; SE) are not well understood. This study examined the effects of enhanced expectancies on motivational state and motor learning in individuals with high and low SE by manipulating the type of knowledge of results (KR). We selected 60 participants from 251 male undergraduate students, based on their SE level, and assigned them to four groups: (a) Good Performance KR and High SE, (b) Poor Performance KR and High SE, (c) Good Performance KR and Low SE, and (d) Poor Performance KR and Low SE. We asked participants to throw beanbags at a target with their nondominant hand during an acquisition phase (10 blocks of six trials each) and during subsequent retention and transfer tests. During acquisition, the Good KR groups received KR from their three most accurate trials in each training block, whereas the Poor KR groups received KR from their three poorest attempts in each block. We measured accuracy scores and changes in SE as dependent variables. Results showed that KR from good trials, relative to KR from poor trials, led to better accuracy scores during acquisition and retention and transfer tests, independent of participants' initial SE levels. Moreover, KR on good trials enhanced SE in the Good KR and Low SE group and kept SE at a high level in the Good KR and High SE group during acquisition and on the retention and transfer tests. These results provide support for the OPTIMAL (optimizing performance through intrinsic motivation and attention for learning) theory of motor learning, and we discuss results in terms of the potential effects of positive feedback on motor performance in professional athletes.